Influence of Au alloying on solid state dewetting kinetics and texture evolution of Ag and Ni thin films - Dierner, Martin; Will, Johannes; Landes, Michael; Volland, Christian; Branscheid, Robert; Zech, Tobias; Unruh, Tobias; Spiecker, Erdmann (Surfaces and Interfaces, 2024)
In this contribution, the effect of Au alloying on the solid state dewetting (SSD) kinetics and texture evolution of AuNi and AuAg thin films is investigated. For that bilayers of a high (AuNi) and low (AuAg) atomic mismatch system are fabricated on different substrates and annealed utilizing a rapid thermal annealing furnace. Afterwards, the degree of SSD, as well as the texturing, are investigated by correlating X-ray diffraction and electron microscopy techniques. A quantitative texture analysis yields that pure metal films (Ni, Au, Ag) exhibit the same degree of 〈111〉 texturing after SSD. In contrast, a reduced degree of texturing is observed for alloys as well as for pure Ni films on amorphous substrates. The texture loss is less pronounced for AuNi on sapphire which is likely due to in-plane texturing along densely packed directions stabilizing the 〈111〉 out-of-plane texture. Further the effect of alloying on the SSD kinetics is investigated. We found that the SSD kinetics of the low-misfit AuAg system continuously changes with the Au concentration and can be perfectly described by composition dependent hole growth as reflected by the Mullins’ coefficient. In contrast, the high-misfit AuNi system resembles this behaviour only during early stages of SSD. For prolonged annealing times at 850 °C as well as 890 °C a strong deviation is observed, which in particular manifests in the concentration range from 50 at% to 70 at% Au, where a drastic increase in the dewetting rate is observed. The deviation from the Mullins coefficient indicates a shift in the prevailing mechanism, suggesting that this accelerated SSD occurs at compositions where the annealing temperature (T) approaches the melting temperature (Tm), i.e. liquidus line. Indeed, the reduced temperature (T/Tm) exhibits its maximum within the compositional range where accelerated SSD is prominent. Additionally, Au segregation at grain boundaries, an increase in surface anisotropy, and a decrease in surface energy are discussed as stabilizing factors for low and high Au concentrations, respectively.<br
Keywords: Solid state dewetting; Binary alloys; Texture evolution; TEM; XRD; Thermodynamics

Influence of substrate polarity on thermal stability, grain growth and atomic interface structure of Au thin films on ZnO surfaces - Dierner, Martin; Landes, Michael; Will, Johannes; Ziegler, Andreas; Hübner, Sabine; Przybilla, Thomas; Zech, Tobias; Unruh, Tobias; Meyer, Bernd; Spiecker, Erdmann (Acta Materialia, 2025)
The influence of the polarity of ceramic substrates on the structural evolution of thin metal films during annealing at elevated temperatures is investigated, including the competing processes of solid state dewetting (SSD) and grain growth, as well as the atomic structure of the epitaxial interface. For this purpose, Au thin films on polar O-ZnO(0001‾) and Zn-ZnO(0001) surfaces are annealed at elevated temperatures and times. Whereas SSD dominates on the O-terminated surface, pronounced grain growth is observed on the Zn-terminated surface. The texture analysis revealed that up to 600 °C, both samples exhibit a fiber texture with slightly dominating Au(111)[110] || ZnO(0001)[112¯0] orientation relation (OR 2). At 800 °C, Au on Zn-ZnO exhibits a transformation to a mazed bicrystal structure with Au(111)[110] || ZnO(0001)[101¯0] orientation relation (OR 1). Comparison of various interface structures in density-functional theory (DFT) indicates that atomically sharp interfaces between the Au(111) films and the ideal bulk-truncated polar ZnO surfaces are energetically favored for both substrate polarities in excellent agreement with atomically resolved electron microscopy. Due to the larger period of the coincidence site lattice in OR 2, the corresponding interface can be described as semi-coherent with clearly separated misfit dislocations. In contrast, the much smaller period of the (approximate) coincidence site lattice in OR 1 leads to a largely incoherent interface with local reconstructions. However, in the experimental situation, even a small rotational deviation from the perfect OR 1 can introduce an interfacial screw dislocation network superimposed on the incoherent interface structure, effectively making the interface semi-coherent.
CRIS-Team Scopus Importer:2025-01-31
Keywords: DFT; Electron microscopy; Grain growth; iDPC; Interfaces; Solid-state dewetting; Texture